TiO2/Jackfruit peel using solar distiller by use of energy storage (International Journal of Food and Nutritional Sciences, 2021)
Jackfruit peel synthesized by greener via blended with TiO2 nanoparticles. They verified with a variety of concentrations with & without coating of the distiller. Researchers fabricated the experimental setup analysis with the different parameters. Characterization results shows the functional energy additives; surface morphology; structure of chemicals. Its shows the potential values is 19.3 mV and crystalline is 85% 85% FTIR spectroscopy explains the bands of absorptions. Distillate yields of 4.96 L/m2 & 6.12 L/m2 efficiency achieved 102.64%.